Postharvest physiology and hypobaric storage of fresh produce - Burg, Stanley P., 1933- (CABI Pub., 2004)
Hypobaric (low-pressure; LP) storage offers considerable potential as a method for preventing postharvest losses of horticultural and other perishable commodities, such as fruits, vegetables, cut flowers and meat. This book, written by the world's leading authority on hypobaric storage, provides a comprehensive evaluation and documentation of this method, its scientific basis and its uses. The first part of the book provides a detailed account of the metabolic functions of gases and the mechanisms of postharvest gas exchange, heat transfer and water loss in fresh produce. These chapters cover the origins of the LP concept; gas and vapour mass transport; the roles of oxygen, carbon dioxide, ammonia, cyanide and ethylene in pre- and postharvest physiology; in addition to heat transfer and water loss. The effects of hypobaric conditions on postharvest diseases, physiological disorders and insect quarantine are considered, followed by chapters on technical difficulties associated with laboratory hypobaric research, and on the design of hypobaric warehouses and transportation chambers. LP storage requirements for a large number of horticultural commodities (specific fruits, vegetables, cut flowers, cuttings and pot plants) are described. One chapter covers the use of LP storage for meat, with a section on specific commodity requirements (beef, chicken, duck, fish, horse meat, lamb, pork, shrimp and veal). This book is a definitive reference work and will interest academics and professionals in horticulture, plant physiology, pest management, and the shipping and food industries.